Prevalence of Blood Parasites (Trypanosoma spp.) in Snakehead Fish (Channa striata) Collected from a Fish Market in Aceh Besar Regency - Winaruddin Winaruddin; Masda Admi (JURNAL BIOLOGICA SAMUDRA, 2026)
Snakehead fish (Channa striata) is recognized as a functional food due to its high protein and albumin content, which support tissue repair and wound healing. However, its susceptibility to haemoparasite infections, particularly Trypanosoma sp., may affect fish health and quality. This study aimed to determine the prevalence of haemoparasites in Channa striata and analyze associated factors such as sex, size, and body weight. A survey was conducted on 48 randomly selected fish obtained from a fish market in Aceh Besar Regency. Blood samples were collected and examined using Giemsa-stained thin blood smears under a microscope to detect Trypanosoma sp. The results showed that 6 out of 48 fish were infected, with a prevalence of 12.50%. Female fish showed a higher prevalence than males, and infection rates increased with fish size and body weight. In conclusion, haemoparasite infection is present in Channa striata and may influence its health and quality, highlighting the importance of monitoring and management to support its use as a functional food.